An Infant with Persistent Respiratory Failure Associated with Refractory Pulmonary Hypertension: Pulmonary Interstitial Glycogenosis - Tomarelli, Gianfranco; Donoso, Alejandro; Andrades, Francisca; Montes, Soledad (Journal of Child Science, 2022)
Pulmonary interstitial glycogenosis (PIG) is a disease of unknown etiology. It is part of the interstitial lung diseases, corresponding to the compartment of the fetal pulmonary interstitium. It typically presents within the first week of life as refractory respiratory distress with tachypnea and persistent hypoxemia, and it is not associated with glycogen deposition in other organs. Usually, there is a clinical improvement and good prognosis after steroid therapy unless there are associated conditions such as congenital heart disease, pulmonary hypertension, or genetic disorders. We report a case diagnosed by lung biopsy at 4 months of age in a male preterm born, small for gestational age infant, who developed refractory hypoxemia and pulmonary hypertension with fatal outcome. There was no response to steroids and hydroxychloroquine. He was not candidate for extracorporeal membrane oxygenation. PIG should be considered in the differential diagnosis of persistent respiratory distress and hypoxemia despite standard treatment, even after the first month of life.
Keywords: pulmonary interstitium; pulmonary interstitial glycogenosis; interstitial lung disease; pulmonary hypertension; respiratory failure